TRIMETHOPRIM-SULFAMETHOXAZOLE AND SODIUM VALPROATE-INDUCED TOXIC EPIDERMAL NECROLYSIS: A CASE SERIES - SRIVASTAVA, BHAVANA; KHANCHANDANI, RENU; DHAPOLA, VIKRAM SINGH; ANSARI, ZAFAR MASOOD (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Toxic epidermal necrolysis (TEN) is a rare and serious but life-threatening dermolytic cutaneous reaction characterized by diffuse and severe exfoliation and destruction of the epidermis of skin and mucosa due to immunological damage of the epidermis which can bring about sepsis and respiratory distress. Drugs are the most common inflicting agents in the generation of TEN. Among drugs, antiepileptics, antipsychotics, and sulfa-drugs are common causes of TEN. Valproate is one of the most common drugs prescribed for epilepsy, was found as causative agent in TEN in very few cases. Among sulfonamides, sulfamethoxazole is commonly used antibiotic which can cause TEN. The evidence-based treatment guidelines are lacking, so the best approach is to recognize and evade potential risk factors and to deliver intensive supportive care immediately to reduce morbidity and mortality. The aim of this case series is to focus on valproate and trimethoprim-sulfamethoxazole (TMP-SMX)-induced TEN, which are commonly used drugs. Here, we present a case series of TEN inflicted by TMP-SMX and sodium valproate in a 23-year-old female and 10-year-old boy, respectively, with successful recovery.